Interactive learning module for Android based devices - Wong, Yoke Meng (2014)
This report presents the final year project - Interactive Learning Module for Android Based Devices that have spanned over 2 academic semesters. Design, implementation, debugging and deployment are essential procedures to ensure that the project is on schedule and is near completion at the end of the Final Year Project.